Development of doubled haploid inducer lines facilitates selection of superior haploid inducers in maize - Chen, Yu-Ru; Lübberstedt, Thomas; Frei, Ursula K (Frontiers in Plant Science, 2024)
Haploid inducers are key components of doubled haploid (DH) technology in maize. Robust agronomic performance and better haploid induction ability of inducers are persistently sought through genetic improvement. We herein developed C1-I inducers enabling large scale in vivo haploid induction of inducers and discovered superior inducers from the DH progenies. Haploid induction rate (HIR) of C1-I inducers ranged between 5.8 and 12.0%. Overall, success rate of DH production was 13% on average across the 23 different inducer crosses. The anthesis-silking interval and days to flowering of inducer F1s are significantly correlated with the success rate of DH production (r = -0.48 and 0.47, respectively). Transgressiveon segregants in DH inducers (DHIs) were found for the traits (Days to flowering, HIR, plant height and total primary branch length). Moreover, the best HIR in DHIs exceeded 23%. Parental genome contributions to DHI progenies ranged between 0.40 and 0.55, respectively, in 25 and 75 percentage quantiles, and the mean and median was 0.48. The allele 2 This is a provisional file, not the final typeset article frequency of the four traits from inducer parents to DHI progenies did not correspond with the phenotypic difference between superior and inferior individuals in the DH populations by genomewide Fst analysis. This study demonstrated that the recombinant DHIs can be accessed in large-scale and used as materials facilitating the genetic improvement of maternal haploid inducers by in vivo DH technology.